Not ready, not set…discharge: Patient‐reported barriers to discharge readiness at an academic medical center. Issue 9 (15th April 2016) - Harrison, James D.; Greysen, Ryan S.; Jacolbia, Ronald; Nguyen, Alice; Auerbach, Andrew D.
Abstract : BACKGROUND: Planning for discharge from the hospital should begin early in each patient's stay and focus on the patient's needs. OBJECTIVE: To determine how often patient‐reported barriers to discharge on admission were resolved by discharge and to explore associations between barriers and readmission. DESIGN, SETTING, AND PARTICIPANTS: A prospective observational study of patients admitted to an academic medical center. INTERVENTION AND MEASUREMENTS: Patients completed a barriers to discharge survey from the start of hospitalization to discharge. Primary outcomes were the prevalence of discharge barriers, rates of resolution of barriers during hospitalization, and comparisons between barriers identified in admission and discharge surveys. RESULTS: One hundred sixty‐three patients were enrolled, and 68 patients (42%) completed an admission survey and discharge survey ≤48 hours before discharge. Patients completed on average 1.82 surveys (standard deviation, 1.10; range, 1–8). Total and mean numbers of barriers were highest on the admission survey and decreased until the fourth survey. On average, the total number of barriers to discharge decreased by 0.15 (95% confidence interval: 0.01‐0.30) per day ( P = 0.047). Ninety percent of patients were discharged with at least 1 issue. The 3 most common barriers on the admission and discharge survey remained the same: pain, lack of understanding of recovery plan, and daily‐living activities. CONCLUSIONS: Patient‐reported barriers to discharge are prevalent and incompletely addressed. This suggests an opportunity for improved discharge planning and a framework for communication between providers and patients. Journal of Hospital Medicine 2016;11:610–614. © 2016 Society of Hospital Medicine